A novel calcium‐accumulating peptide/gelatin in situ forming hydrogel for enhanced bone regeneration. Issue 2 (30th October 2017) - Jo, Beom Soo; Lee, Yunki; Suh, Jin Sook; Park, Yoon Shin; Lee, Hyun Jung; Lee, Jue‐Yeon; Cho, Jaejin; Lee, Gene; Chung, Chong Pyoung; Park, Ki Dong; Park, Yoon Jeong
Abstract: Bioactive agents, including proteins and peptides, can be loaded into hydrogels to improve bone regenerative capacity with their controlled release. However, the current loading method has focused on physical mixing, which has limited release control. Therefore, alternative conjugation of bioactive agents with hydrogels is highly recommended. Direct chemical conjugation of synthetic peptides containing a functional moiety with a hydrogel would be ideal. Here, we synthesized a bioactive calcium accumulating peptide (CAP) containing a collagen binding motif, which can induce osteogenic differentiation. A tyrosine residue in CAP was used to directly chemically conjugate the peptide with a gelatin‐based enzymatically crosslinked hydroxyphenyl propionic acid hydrogel under H2 O2 /Horse radish peroxidase conditions. To test the acceleration of bone formation, human periodontal ligament stem cells (PDLSCs) were loaded into a chemically conjugated CAP hydrogel. The CAP hydrogel induced bone mineralization around the PDLSCs and increased osteogenic marker expressions in vitro . It also recovered a bone layer in a calvarial defect 4 weeks postimplantation. In summary, an injectable CAP hydrogel scaffold system was developed as a potentially useful engineered microenvironment to enhance bone restoration, and it could be utilized as a vehicle for bioactive delivery of stem cells in tissue regenerative therapy. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 531–542, 2018.